LAYANAN INFORMASI PEMBAYARAN BIAYA KULIAH BERBASIS SMS GATEWAY - Siti Hijratul Jihadah Marzuki; Muhammad Azmi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2021)
SMS (Short Message Service) Gateway is an SMS-based system that can be developed in various fields and utilizes a web-based programming language. At STMIK XYZ, the delivery of information about the schedule for tuition payments is still by placing announcements / banners in the campus environment and sending letters to parents / guardians. These methods are not optimal because of the limitations of delivery to students and sometimes students do not pay attention to them. This is evident from the many students who are late in making tuition payments. Therefore, a system / application is needed that can provide services that can be accessed by students and parents / guardians to find out the status of their son / daughter's college payment. The design and manufacture of the SMS gateway-based tuition payment service system uses the Waterfall methodology, which is a software development method that begins with analyzing company needs, designing, building applications, to conducting trials. This tuition payment service system sends SMS to students and parents about the schedule of tuition payments and the status of payments that have been made. Information and payment status is sent to the cellphone number of each student and parent / guardian and provides warning information 7 (seven) days before the payment deadline. This application can also generate various types of reports regarding the status of student tuition payments to management. With this application / system, it is hoped that it can assist the management in accelerating the delivery of information about the schedule and status of student tuition payments.